أثر تقديم درس في مادة التاريخ الإسلامي وفق الذكاءات المتعددة على التحصيل الدراسي لطالبات الصف الحادي عشر الثانوي أدبي في منطقة مبارك الكبير التعليمية بدولة الكويت - السنافي، سامية (جامعة الإسكندرية - كلية رياض الأطفال, 2012)
هدفت هذه الدراسة إلى تقصي أثر استخدام إستراتيجية الذكاءات المتعددة في التدريس على تحصيل طالبات الصف الحادي عشر الثانوي في مادة التاريخ الإسلامي. \ تكونت عينة الدراسة من (٩٦) طالبة من طالبات الصف الحادي عشر الثانوي من ثانوية فارعه بنت أبي الصلت في منطقة مبارك الكبير التعليمية من الفصل الدراسي الثاني للعام الدراسي 2011/ 2012، تم تقسيمه إلى مجموعتين: تجريبية (٤٨) طالبة، درست باستخدام إستراتيجية الذكاءات المتعددة، وضابطه (٤٨) طالبة درست باستخدام الطريقة التقليدية المعتادة، تم تصميم اختبار تحصيلي عن المستويات المعرفية الستة وبلغ مجموع درجات الاختبار (١٠٠) درجة. وكشفت نتائج الدراسة الآتي: \ تفوق استراتيجيه التدريس القائمة على الذكاءات المتعددة على الطريقة التقليدية، حيث بلغ المتوسط الحسابي للمجموعة التجريبية (81.25) وهو يفوق المتوسط الحسابي للمجموعة الضابطة والذي بلغ (74.94). \ هناك فرق ذو دلالة إحصائية في تحصيل عينة الدراسة بلغت (0.002)، تعزى لمتغير استراتيجيه الذكاءات المتعددة ولصالح المجموعة التجريبية. \ وخلصت الدراسة إلى عدد من التوصيات ركزت على: ضرورة إعادة تشكيل وصياغة المناهج الدراسية في ضوء الذكاءات المتعددة، وتطوير برامج إعداد معلمي المرحلة الثانوية بكليات التربية بحيث تشمل استراتيجيات الذكاءات المتعددة مع عمل دورات تد ربيبة للمعلمين والموجهين على حد سواء لاستخدام هذه الإستراتيجية مع ضرورة الابتعاد عن الطرائق التقليدية في تدريس التاريخ وإتاحة الفرصة للمتعلم لممارسة الأنشطة الصفية واللاصفية بجو ممتع قائم على استراتيجيه الذكاءات المتعددة مع ضرورة إعادة النظر في نظام التقويم لطلبة المرحلة الثانوية في المدارس وتعميم نظام القويم بالذكاءات المتعددة. This study aimed to verify the effect of using multiple intelligences strategy in teaching on achievement of female students at llth secondary class in the subject of Islamic history. \ Study sample consists of 96 female students from 11th secondary class at Farea Bint Abi Al- Salt Secondary' School at Mubarak Al- Kabcer Educational Area from the second term for the academic year 2011/2012, divided into two groups: experimental group of 48 students, which studied using multiple intelligences, and a control group of 48 female students which studied with the traditional method, an achievement test is designed on the six cognitive level with total test score of 100 degrees, and the statement of study results was as follows: \ 1.\ Excellence of teaching strategy based on multiple intelligences more than the traditional method, where the arithmetic mean of the experimental group reached 81.25, i.e. more than the arithmetic mean of the control group which reached 74.94. \ 2.\ There is a statistically significant difference in achievement of the study sample reached (0.002) ascribed to the variable of multiple intelligences strategies, for the interest of the experimental group. The study concluded some recommendations con¬centrated on the following: necessity to reform and formulate educational curricula in the light of multiple intelligences, and development of a program for preparing teachers of the secondary school at faculties of education so as to include strategies of multiple intelligences with training courses for teacher and instructors equally to use this strategy with necessity to be away from traditional methods in teaching history and providing the chance for learner to practice \ classroom and non- classroom activities in an atmos¬phere of enjoyment based on multiple strategies with necessity to reconsider the system of evaluation for students of secondary level at schools and to generalize the system of evaluation by multiple intelligences
Keywords: طالبات المدارس الثانوية -- تدريس التاريخ الإسلامي -- معلمو التاريخ -- طرق التدريس -- الذكاءات المتعددة -- التحصيل الدراسي -- سلوك الطالبات -- البرامج التعليمية -- الكويت